Agama dan Negara dalam Konteks Keindonesiaan - Arfan Arfan; Indo Santalia; Tabhan Syamsu Rijal; Nur Afni A. (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
This study analyzes the relationship between Islam and the state in the Indonesian context. This research employes descriptive and analytical methods through normative and historical approaches, through literature review, both books written by classical scholars as well as books and journal articles written by contemporary researchers, and other relevant sources. The results of this study indicate that the relationship between religion and the state in the Indonesian context initially led to an integral paradigm by making Islam the basis of the state. However, with various considerations, Pancasila is the middle way which marks that the state and the Islamic religion are in a symbiotic paradigm. To this day, the two side by side help each other in achieving the national ideals of the Indonesian nation.